Trends in Group A Streptococcus Pharyngitis and Co-Infection with Severe Acute Respiratory Syndrome Coronavirus 2: A Retrospective Observational Study - Takahashi, Hidenori; Satake, Yugo; Shimizu, Saori; Fujihara, Satomi; Takano, Syunsuke; Fukasawa, Suzuko; Park, Kaeyong; Toba, Naoya; Yano, Takahiko; Nagamatsu, Hiroki; Hirose, Ryutaro; Toyama-Kousaka, Mio; et al. (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: Group A Streptococcus (GAS) is a leading cause of acute pharyngitis with seasonal outbreaks. The coronavirus disease 2019 (COVID-19) pandemic significantly altered respiratory infection trends; however, its impact on GAS pharyngitis (GAS-P) incidence remains unclear. Additionally, data on co-infections with GAS and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are limited. In this study, temporal trends in GAS-P incidence and characteristics of GAS–SARS-CoV-2 co-infections in Japan were examined. Materials and Methods: In this observational study, data from patients who visited the Tokyo Shinagawa Hospital between January 2019 and December 2024 were retrospectively analyzed. Data on GAS and SARS-CoV-2 test results and patient demographics were extracted from medical records. The study period was categorized based on COVID-19-related public health measures as follows: pre-COVID-19 social period (January 2019–April 2020), restricted social period (May 2020–April 2023), and post-restriction period (May 2023–December 2024). GAS incidence stratified by sex, age, and period was calculated. Clinical characteristics of patients co-infected with GAS and SARS-CoV-2 were analyzed. Results: Among 4837 GAS tests, 463 (9.6%) were positive. GAS positivity rates varied significantly: 11.4% (pre-COVID-19), 7.1% (restricted social period), and 12.6% (post-restriction period; p < 0.001). The proportion of pediatric cases decreased significantly during the restricted social period (24.8–5.3%) before rising sharply in the post-restriction period (47.1%, p < 0.001). Among 151 patients tested for GAS and SARS-CoV-2, 14 (9.3%) had co-infections, which were identified exclusively after July 2022. Most patients exhibited mild symptoms, primarily fever and sore throat, with decreased lymphocyte counts despite normal white blood cell counts. Conclusions: In our cohort, the incidence of GAS pharyngitis temporarily declined during COVID-19-related public health measures and subsequently increased, particularly among children, after restrictions were lifted. Limited testing may contribute to the underdiagnosis of GAS–SARS-CoV-2 co-infections. Further large-scale studies are warranted to assess microbial interactions, disease severity, and long-term outcomes.